Bond behavior of the CFRP-concrete interface under combined sustained load and sulfate erosion. (January 2022) - Zhang, Jiawei; Li, Hang; Liu, Shengwei; Zhang, Xiangyan; Yang, Chenghong; Zhang, Rongling
Abstract: The interface bonding between carbon fiber-reinforced polymer (CFRP) and concrete plays a key role in the reinforcement of concrete structures using CFRP. However, in practical engineering, the reinforced structure is often subjected to the effect of sustained load and corrosive environmental conditions. The lack of sufficient research on the long-term performance of the bond interface under these conditions will hinder its application in the repair of aging structures. In this study, 27 double-sided shear specimens of CFRP-strengthened concrete were designed and fabricated, and the tests were performed under the combined action of sustained load and sulfate dry-wet cycles. The combined effects of erosion days and sustained load levels on failure modes, bearing capacity, stress and strain, and bond - slip curves of reinforced structures were studied. Based on the results, the failure mode of the reinforced structure gradually changes from shear failure of the concrete to debonding failure of the bond interface. The ultimate load and the stress-strain curve of CFRP showed an overall downward trend, and the degradation degree further increased with the increase in loading level. Through the inductive analysis of the experimental data, a bond-slip model of the interface considering the combined effect was proposed for these working conditions. Compared with the experimental curve, this model can sufficiently predict the degradation of the interface bond performance under the combined exposure to sustained load and sulfate dry-wet cycles.